(3cJGH LGdjfhS Edi CZdhbf aj GdJCJi dTaGA GdCeQGVs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3Efg djS jfHZi ddWHjH Cf jbJUQ Ydi eYQaI GdWHjYjI GdJi JYe LejY GdfGS SG CZdhbf Ohf Cf jYQa GdWHjYI GdJi JNU cd hGMO ef GdfGS s
(3BNQgG (B:s
(3dCf CUMGHi bO SCdhfi Pdc hEf WGd dHKc HGdHYO YfG hJCNQ bOhec adjSJ CZad Yf GdHZjI Edjc HeG CcJH Hg ef Pdc ChdG HChd Ef TGA Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdfSNI HgG MhGTs
(3bhHdJ HCUdjf SfI (B692(3g`s
(3hHgG eTgG HYV GdJUMjMGJs
(3hGfXQ (B22 (3ef agQS GdWH HYfhGf (B: (3cJGH Edi s
(3hgh GdcJGH GdQGHY ef cJH GdSJI YTQ dLGdjfhS GdJi cGfJ JbQC Ydi GdeYdejf HGdEScfOQjI s
(3hbO hVYg ai ebGdJjf Hjf ajgeG OdGFd GdCeQGV GdJi JYQa HgG bHd eOGhGJgG s
Keywords: (3GdWHs